2016
DOI: 10.5539/gjhs.v9n5p18
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Acceptance and Commitment Therapy (ACT) on Self-Efficacy, Perceived Stress and Resiliency in Type II Diabetes Patients

Abstract: Introduction: The prevalence of diabetes, especially type II diabetes, is increasing in the world. It seems that psycho-cognitive factors such as perceived-stress and resiliency can play an important role in diabetes care. The aim of the present study is examining the effect of Acceptance and Commitment Therapy (ACT) on self-efficacy, perceived stress and resiliency in type II diabetes patients. Methods:The method of this research was quasi-experimental (pre-test, post -test) with follow-up stages. The populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
(20 reference statements)
0
22
0
1
Order By: Relevance
“…Regarding the natural emotion in responding illness, individuals cannot avoid the negative thoughts. Individuals practice in organizing the negative thoughts with stopping spontaneous reactions such as crying, feeling sad and hopeless (Khashouei, Ghorbani, & Tabatabaei, 2016). ACT is effective in a wide range of population, such as breast cancer, (Mahdavi et al, 2017), DM type-II (Gregg, Callaghan, Hayes, & Glenn-Lawson, 2007;Lindholm-Olinder et al, 2015), and multiple sclerosis (Bach, Hayes, & Gallop, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the natural emotion in responding illness, individuals cannot avoid the negative thoughts. Individuals practice in organizing the negative thoughts with stopping spontaneous reactions such as crying, feeling sad and hopeless (Khashouei, Ghorbani, & Tabatabaei, 2016). ACT is effective in a wide range of population, such as breast cancer, (Mahdavi et al, 2017), DM type-II (Gregg, Callaghan, Hayes, & Glenn-Lawson, 2007;Lindholm-Olinder et al, 2015), and multiple sclerosis (Bach, Hayes, & Gallop, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 6351 records were eligible for the title and abstract screening. Full-text screening of 35 studies yielded 22 eligible studies [20][21][22][23][24][25][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. After a quality appraisal, seven studies [25,[41][42][43][44][45][46] were excluded following a collective agreement between authors that the quality of the studies was too low to merit inclusion.…”
Section: Study Inclusionmentioning
confidence: 99%
“…Recent studies on ACT have shown its efffectiveness for the treatment of depression [18], post-traumatic stress disorder [19], panic disorder [20], chronic pain [8], obsessive-compulsive disorder [23], breast cancer [24], multiple sclerosis [25], diabetes [26,27], abnormal grief [28], and reducing job stress [22].…”
Section: Introductionmentioning
confidence: 99%